Ordforbindelser: Grunnelementer i ordboken? - Jónsson, Jón Hilmar (LexicoNordica, 2009)
The article describes the construction of a lexicographic description where different types of phraseological units have a wider and more active role than is usually the case in traditional dictionaries. It relates how the description of Icelandic phrasemes and collocations has been assembled in stages, starting with a printed combinatory dictionary, going towards an electronic dictionary description. A large collection of phrasemes and colloactions has been used to identify and analyse lexical and semantic relations, and on the basis of such an analysis to classify the vocabulary according to semantic features. Moreover, the phrasemes have been widely lemmatised on a level with single words which makes it possible to pinpoint their semantic relations to single-word lemmas. Additionally, as the multi-word lemmas have a standard presentation form, the lemma strings can be grammatically tagged and categorised by syntactic constructions. A lexicographic model of this sort is based on the onomasiological standpoint. The lemmas are generally unambiguous and the description combines different roles that have usually been fulfilled by different types of dictionaries.